An Overcoming Red Indicator Alarm Disruptions Server 2 AMSC Comsoft in a Public Company, Palembang Branch - Suherman, Suherman (SEAN Institute, 2024)
Security officers often cannot monitor the security of the financial room at any time, especially outside working hours or at night because the financial room is in a special room. Security officers do not receive warnings quickly if someone who does not have the right to enter the financial room when it is empty or outside working hours. The aim of this research is to design an application that can monitor the security of the financial room by providing information or giving warnings in the form of alarms. and sending SMS and Twitter notifications to security officers if someone who does not have access rights enters the financial room, using the DFRduino UnoR3 microcontroller, MC-38 magnetic sensor, PIR sensor, alarm, Sony Ericsson Z530i cellphone, wifi modem, and Bluetooth. If a door opening or movement is detected, the computer will send a command to the DFRduino which is then forwarded to the alarm to provide a sound warning. And with an Android cellphone with a connection via the GSM network, it can be connected to the application so that the computer can send warning notifications to the number that has been registered as the recipient of the notification via Twitter to the username that has been registered. With the magnetic sensor it is possible to detect if a door or window has been forced open and The PIR sensor is used as a support if the magnetic sensor does not work or if the thief enters the room not through a door or window. PIR sensors installed indoors allow all activities that occur to be monitored properly.